Preliminary Evidence for a Nexus between Rumination, Behavioural Avoidance, Motive Satisfaction and Depression. (26th January 2014) - Brockmeyer, Timo; Holtforth, Martin Grosse; Krieger, Tobias; Altenstein, David; Doerig, Nadja; Zimmermann, Johannes; Backenstrass, Matthias; Friederich, Hans‐Christoph; Bents, Hinrich
<x xml:space="preserve">Abstract</x> The present study tested a theoretically derived link between rumination and depressive symptoms through behavioural avoidance and reduced motive satisfaction as a key aspect of positive reinforcement. Rumination, behavioural avoidance, motive satisfaction and levels of depression were assessed via self‐report measures in a clinical sample of 160 patients with major depressive disorder. Path analysis‐based mediation analysis was used to estimate the direct and indirect effects as proposed by the theoretical model. Operating in serial, behavioural avoidance and motive satisfaction partially mediated the association between rumination and depressive symptoms, irrespective of gender, medication and co‐morbid anxiety disorders. This is the first study investigating the associations between behavioural avoidance, rumination and depression in a clinical sample of depressed patients. The findings are in line with an understanding of rumination in depression as also serving an avoidance function. Copyright © 2014 John Wiley & Sons, Ltd. Key Practitioner Message Rumination, avoidance, motive satisfaction and levels of depressive symptoms were examined in a clinical sample of 160 outpatients with major depressive disorder. Path analysis‐based mediation analysis revealed that, operating in serial, avoidance and motive satisfaction partially mediated the link between rumination and levels of depressive symptoms. Findings support an understanding of rumination in depression as serving an avoidance function.